PUKPARA; A Digital Platform Enabling the Scaling of AICCRA’s Climate-Smart Integrated Pest Management (CS-IPM) Bundle in Ghana - Offei-Asare, Priscilla; Dalaa, Mustapha Alasan; Obeng Adomaa, Faustina (2025)
This brief summaries the use of PUKPARA digital platform to scale CS-IPM solutions to farmers highlighting its integration with AICCRA’s Ag-Innovation Data Hub (AIDH) which presented further opportunities for robust extension support to farmers.